Abdominal etching - Maurício Schneider Salomone Viaro (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Abdominal etching involves improvement of the appearance of the abdominal musculature by removing fat from several skin layers, including the superficial layer. This study evaluated the aesthetic results of abdominal etching using liposuction. Methods: The aesthetic results and surgical complications of female patients were evaluated between 2017 and 2018. All study patients answered a standard questionnaire about the extent of improvement in body image, overall satisfaction level, naturalness of the result, and changes in exercise and dietary habits. Results: The mean patient age was 38.97 years, while the mean body mass index was 24.01. In our sample, 75% of the subjects had previous pregnancies, 25% had previous abdominal surgeries, and 2.5% had a history of smoking. Simultaneous surgeries were performed in 90% of cases. The following surgery types were performed: liposuction alone (40.00%), liposuction + abdominoplasty (36.25%), miniabdominoplasty (12.50%), abdominoplasty + liposuction (10.00%), and reverse abdominoplasty (1.25%). Moderate aesthetic improvement was observed in 86.25% of the patients, and surgical complications occurred in eight patients. The satisfaction rate was 91.7%, and the result was classified as natural by 97.5% of the patients. Conclusion: Abdominal etching promoted high patient satisfaction and achieved a natural appearance of the abdomen. This surgical outcome was achieved using conventional liposuction without the need for additional techniques. However, further studies are needed to evaluate long-term outcomes.